Mediation of Job Satisfaction on the Effect of The Big Five Personality on Employee Performance - Agustina; Ririn Handayani; Helwen Heri (Yayasan Education Al Aqsho Modern, 2022)
The purpose of this study was to determine the effect of the big five personality on employee performance with job satisfaction belief as a mediating variable. Population and sample are State Civil Apparatus of Department of Manpower and Transmigration Indragiri Hilir Regency totaling 32 people. Data collection techniques using questionnaires. Technical data analysis in this study is Structural Equation Modeling (SEM) using Smart PLS 3.2.9 for data processing. The results of this study are the big five personality affects employee performance positively and significantly. Job satisfaction affects performance positively and significantly. Job satisfaction is proven to be a mediation in the relationship of the big five personality to employee performance.